Modifiable risk factors for stillbirth: a literature review. (December 2019) - Escañuela Sánchez, Tamara; Meaney, Sarah; O'Donoghue, Keelin
Highlights: Some behaviours have been associated with a higher risk of stillbirth. Smoking and illicit drug use have the highest impact on the risk of stillbirth. Maternal weight is an independent risk factor but it can lead to other issues. Lack of attendance to antenatal care has also been associated with higher risk. Sleeping position is possibly the most modifiable risk factor associated with stillbirth. Abstract: A stillbirth is defined as an infant born weighing 500 g and/or more or at a gestational age of 24 weeks who shows no signs of life. Having a stillborn baby has a wide range of consequences that can affect parents, family and the healthcare professionals involved. Several risk factors have been associated with an increased risk of stillbirth: including maternal medical factors, maternal characteristics, fetal factors, sociodemographic factors and behavioral factors. The aim of this work is to review the literature on risk factors that have a behavioral component. The main behaviors modulating the risk of stillbirth that have been more widely studied in the literature include use of substances (smoking, alcohol, illicit drugs and medical drugs), weight management, attendance at antenatal care and sleeping position. There is evidence in the literature that supports that all those behaviors have an impact on the risk of stillbirth, especially in the cases of smoking and drugs consumption during the pregnancy. Hence, more research is needed to establish interventions targeting these behaviors as preventive measures to reduce the risk of adverse obstetric outcomes.